Service Marketing, Trust And Company Image On Satisfaction And It’s Impact On The Loyalty Of Umrah Pilgrims In Palembang - Yudha Mahrom Darma Saputra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Umrah travel service industry in Palembang  was long provided and dedicated to the community of Palembang. The provider of Umrah service hope all residents of Palembang to increase  faith and piety to Allah. Based on the initial research result, it’s identified that there wewr several problems on customers with less-loyalty to the provider of umrah service industry.The purpose of this study is develop model of service marketing for umroh/pilgrim customers. We do analysis the effect  of their loyalty on the satisfaction of the service provide for umrah customer whether it’s true or not.The research design used descriptive statistic to analyse topic of research on 20 umrah travel providers which have met the requirements. We have  200 respondents as population from 20 companies and taken 10 respondents respectively.The data was primarily   collected from questionnaires that have been validated about its reliability.  The analytical tools  of this study is SEM with Lisrel Application.  The end of this research concludes that the service marketing management practices, trust, company image, pilgrim satisfaction and pilgrim loyalty need to be improved. The outcomes of this research atates that causality analysis is used to present  a) the loyalty of umroh pilgrims in Palembang is strongly influenced by consumer’s trust and company image; b) services marketing could not proven as direct variable, because of service marketing to have no effect on consumer satisfaction, consumer’s trust, corporate image and consumer’satisfaction that could be proven that the service marketing is influence by consumer loyalty